DOI 10.1007/s00382-012-1297-0 The role of forcing and internal dynamics in explaining the ‘‘Medieval Climate Anomaly’’ - D. Shindell; H. Renssen; M. E. Mann; Y. Sallaz-damaz; H. Goosse; Drew Shindell; Yoann Sallaz-damaz; Hans Renssen; Michael E. Mann; Marie-france Loutre; Clim Dyn; Hugues Goosse; et al. (2011)
Abstract Proxy reconstructions suggest that peak global temperature during the past warm interval known as the Medieval Climate Anomaly (MCA, roughly 950–1250 AD) has been exceeded only during the most recent decades. To better understand the origin of this warm period, we use model simulations constrained by data assimilation establishing the spatial pattern of temperature changes that is most consistent with forcing estimates, model physics and the empirical information contained in paleoclimate proxy records. These numerical experiments demonstrate that the reconstructed spatial temperature pattern of the MCA can be explained by a simple thermodynamical response of the climate system to relatively weak changes in radiative forcing combined with a modification of the atmospheric circulation, displaying some similarities with the positive phase of the so-called Arctic Oscillation, and with northward shifts in the position of the Gulf Stream and Kuroshio